Global citizenship education in primary school: a comparative analysis of education policy documents in Portugal and Spain - Santamaría-Cárdaba, Noelia; Lourenço, Mónica (Iberoamerican Journal of Development Studies, 2021)
In this study it is investigated whether, to what extent, and how the education policy documents of Portugal and Spain aimed at the first years of schooling are responding to international calls to educate critical and responsible citizens. To do this, a qualitative methodology was adopted in the analysis of the documents that regulate the six to ten years old curricula in both countries. Data was analysed using content analysis, with categories deriving from the UNESCO (2015) framework on global citizenship education (GCE) dimensions and key learner attributes. Results suggest that the curricula for the first years of schooling of both countries are compatible with the principles of GCE. Yet, strong additional efforts are required for a successful implementation of this educational perspective in the long run.